Friction tests on polyurethane and concrete. Rolling friction tests and sliding friction tests on anti-abrasion polyurethane, anti-seepage polyurethane and concrete. - Hansen, Kristian (UiT The Arctic University of Norway, 2018)
The climate in arctic areas of the world is a challenge for airports. Snow and ice accumulates on the runways, forcing airports to close for snow clearing. Pilots need to know that the friction is at a respectable level before they land, and may have to return if not. This thesis looked at a polymer called polyurethane, and if this material could be used as a new runway material, considering both rolling friction and sliding friction. There were tested two types of polyurethane. It also looked into how ice on top of polyurethane behaved when a car was driven over the material, compared to concrete. The results from the tests showed that there was no difference in friction when the testing was done with ice on top of the materials. Rolling friction without ice gave a higher coefficient of friction for both types polyurethane compared to concrete. From the sliding friction tests, one could see that one type of polyurethane had almost the same coefficient of friction as concrete, and the other polyurethane got a higher coefficient of friction. The ice breaking test showed that it is much easier to remove ice from polyurethane, compared to concrete.